Scar identification, quantification, and characterization in complex atrial tachycardia: a path to targeted ablation?. (25th February 2019) - Laţcu, Decebal Gabriel; Bun, Sok-Sithikun; Casado Arroyo, Ruben; Wedn, Ahmed Moustfa; Benaich, Fatima Azzahrae; Hasni, Karim; Enache, Bogdan; Saoudi, Nadir
Abstract: Successful catheter ablation of scar-related atrial tachycardia depends on correct identification of the critical isthmus. Often, this is a represented by a small bundle of viable conducting tissue within a low-voltage area. It's identification depends on the magnitude of the signal/noise ratio. Ultra-high density mapping, multipolar catheters with small (eventually unidirectional) and closely-spaced electrodes improves low-voltage electrogram detection. Background noise limitation is also of major importance for improving the signal/noise ratio. Electrophysiological properties of the critical isthmus and the characteristics of the local bipolar electrograms have been recently demonstrated as hallmarks of successful ablation sites in the setting of scar-related atrial tachycardia.